HDA19-mediated deacetylation of histone H3.3 at lysines 27 and 36 regulates plant sensitivity to salt stress - Florian Kotnik; Minoru Ueda; Akihiro Ito; Junko Ishida; Satoshi Takahashi; Katsuyuki Sakai; Hiroshi Takagi; Julian Seidel; Takahiro Abe; Jürgen Eirich; Shunji Takahashi; Dirk Schwarzer; et al. (Proceedings of the National Academy of Sciences, 2026)
Plants survive extreme environments through rapid chromatin reprogramming, yet the epigenetic marks that confer stress resilience remain poorly understood. Histone deacetylase HDA19 is a key epigenetic regulator in Arabidopsis, and hda19 -deficient mutants display tolerance to multiple abiotic stresses, including drought, heat, and salinity. Using lysine acetylome profiling, we identified a noncanonical K27/K36 diacetylation mark on histone H3.3, among nine H3 variants, as a specific substrate of HDA19. Under salinity stress, this mark decreased in wild-type plants but increased in hda19 mutants, while other known H3 modifications were similarly affected in both genotypes. Mimicking constitutive diacetylation of H3.3K27/K36 through lysine-to-glutamine substitutions promoted accumulation of stress-responsive late embryogenesis abundant (LEA) proteins and conferred salinity tolerance in seedlings, phenocopying hda19 mutants. Furthermore, generating the lea7-1/lea29-1/rab18-1 triple mutant abolished hda19 -dependent salinity tolerance, confirming the LEA proteins’ role downstream of HDA19. Our findings demonstrate that H3.3K27/K36 diacetylation, modulated by HDA19, drives LEA protein accumulation and enables plants to withstand environmental stress, revealing a core mechanism of plant stress resilience.